2016
DOI: 10.3389/fimmu.2016.00428
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Interstitial Migration: Motility Cues from the Inflamed Tissue for Micro- and Macro-Positioning

Abstract: Effector T cells exit the inflamed vasculature into an environment shaped by tissue-specific structural configurations and inflammation-imposed extrinsic modifications. Once within interstitial spaces of non-lymphoid tissues, T cells migrate in an apparent random, non-directional, fashion. Efficient T cell scanning of the tissue environment is essential for successful location of infected target cells or encounter with antigen-presenting cells that activate the T cell’s antimicrobial effector functions. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 134 publications
1
42
0
Order By: Relevance
“…Following TEM, T cells encounter a distinct microenvironment, where a combination of soluble mediators, cell-cell, and cell-extracellular matrix (ECM) interactions influence micropositioning within the tissue (32). While collagen type I is thought to be widely distributed throughout the interstitial space, collagen type IV is predominantly found in the airway epithelium and vascular endothelium (33).…”
Section: Resultsmentioning
confidence: 99%
“…Following TEM, T cells encounter a distinct microenvironment, where a combination of soluble mediators, cell-cell, and cell-extracellular matrix (ECM) interactions influence micropositioning within the tissue (32). While collagen type I is thought to be widely distributed throughout the interstitial space, collagen type IV is predominantly found in the airway epithelium and vascular endothelium (33).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike uterine myometrium and SLOs, the epidermis is densely populated with stationary keratinocytes, which suggests that motility may be partly regulated by tissue architecture 28,29 . Indeed, we found that motility was substantially reduced (~6 μm min −1 ) in the matrix-dense region of the uterine perimetrium.…”
Section: Discussionmentioning
confidence: 99%
“…64 T lymphocytes have to be fast and mobile to reach their goal, and rely on non-proteolytic migration, which does not require matrix proteolysis but rather involves a shape change to enable cells to glide and squeeze through pre-existing matrix defects. 65,66 T cell locomotion generates high energy demands, but equally important are rearrangements of the cellular membranes to allow cells to slip through matrix gaps and trail through connective tissues. 67 A key finding in the examination of abnormal T cell behavior was the recognition that RA T cells are prone to form invasive membrane structures 25 (Figure 6), resembling podosomes and invadosomes utilized by cancer cells when they metastasize.…”
Section: R a T Cell S Los E The Mitochondrial Protec Tor Mre11 Amentioning
confidence: 99%